ОСНОВНЫЕ ЦЕЛИ ПРОФИЛЬНОГО ОБУЧЕНИЯ - Бектурганова, З.К.; Ерекеева, А.С.; Жумамуратов, Р. (SCIENCE and SOCIETY, 2016)
The article considers specialized education with main goals of deep study of separate subjects of programs of complete general education.
Keywords: comprehensive school; specialized education; the meaning of knowledge; physics-chemical; chemical-biological; biological-geographical; agrothechnological concepts